Pengaruh Konten Pemasaran Tiktok Dan Online Customer Review Terhadap Keputusan Pembelian Pada Produk Scarlett Whitening (Mahasiswa Institut STIAMI) - Widyatmoko, Satrio Tito; Yulianto, Yulianto (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Content marketing is a marketing approach that involves developing or creating content that is presented with the aim of informing target buyers. Online customer reviews played an important role in shaping consumer purchasing decisions. It has been explained above that a marketing content in the TikTok application, online customer reviews had an influence on purchasing decisions. The purpose of the research was to determine and analyze how much influence TikTok marketing content and online customer reviews had on purchasing decisions on Scarlett whitening products and the method used was quantitative method with data collection techniques used questionnaires, observation, and literature study. The number of samples in this research were 100 students of Institut STIAMI. From the results of the calculation of the coefficient of determination (R2), the coefficient of determination (R2) value was 0.658 or 65.8%, which meant that the marketing content and online customer review variables on the purchasing decision variable (Y) were 65.8%, while the result of the t-test calculation on the marketing content variable on purchasing decisions obtained the value of t-count > t-table of 3.546 > 1.660 on the online customer review variable on the purchasing decision variable obtained the value of t-count > t-table of 8.737 > 1.660 with each sig value of 0.001 <0.05. However, the F-test result showed that the calculated F-count was 37.781 with a sig value of 0.001. This meant that H3 was accepted, which means that simultaneously there was an influence between the variables of Marketing Content (X1) and Online Customer Review (X2) on Purchasing Decisions on Scarlett Whitening Products.